Coal Fired Power Plant with Chemical Looping Combustion - Surywanshi, Gajanan Dattarao; Patnaikuni, Venkata Suresh (Proceedings of Engineering and Technology Innovation, 2017)
Around 54.7% of the total energy in India is produced from coal-fired power plants. In order to reduce the emission of CO2 into the atmosphere from these power plants, the effluent CO2 needs to be captured and sequestered or utilized. Chemical looping combustion (CLC) is an inherent CO2 capture technique in which coal is reacted with oxygen in the form of metal oxide instead of air and produces concentrated CO2 as a mixture of CO2 and steam. CO2 from this mixture can be easily separated and captured by condensing the steam. In this paper, a CLC integrated coal fired power plant with Fe2O3/Al2O3 as oxygen carrier was simulated using Aspen Plus ® simulation tool and the energy analysis was presented. High ash Indian coal was used in the present work. Results showed that CLC integrated coal fired power plant (CFPP) is more energy efficient with CO2 capture.